2019
DOI: 10.1002/esp.4728
|View full text |Cite|
|
Sign up to set email alerts
|

Partitioned by process: Measuring post‐fire debris‐flow and rill erosion with Structure from Motion photogrammetry

Abstract: After wildfire, hillslope and channel erosion produce large amounts of sediment and can contribute significantly to long‐term erosion rates. However, pre‐erosion high‐resolution topographic data (e.g. lidar) is often not available and determining specific contributions from post‐fire hillslope and channel erosion is challenging. The impact of post‐fire erosion on landscape evolution is demonstrated with Structure from Motion (SfM) Multi‐View Stereo (MVS) photogrammetry in a 1 km2 Idaho Batholith catchment burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 90 publications
(180 reference statements)
4
23
1
Order By: Relevance
“…These measurements are necessary to expand our knowledge of the mechanistic controls on postfire erosional responses considering the significant natural variability that exists in fire‐disturbed landscapes (Moody et al, 2013). Although inferred from previous studies (e.g., Kean et al, 2011; Wells, 1987), the role of decreasing sediment availability can now be explored more fully with the use of high‐resolution change detection techniques such as terrestrial laser scanning (herein referred to as TLS) (e.g., Schmidt et al, 2011; Staley et al, 2014) and unmanned aerial vehicle Structure‐from‐Motion (herein referred to as SfM) (Ellett et al, 2019). TLS methods are able to resolve surface changes down to less than a centimeter such as those associated with widespread hillslope erosion on burned hillslopes (e.g., DeLong et al, 2018; Staley et al, 2014), and UAV‐based SfM is able to resolve changes on the order of a decimeter (e.g., Barnhart et al, 2019; Ellett et al, 2019) that would be associated with the erosion of large rills, gullies, and channels.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements are necessary to expand our knowledge of the mechanistic controls on postfire erosional responses considering the significant natural variability that exists in fire‐disturbed landscapes (Moody et al, 2013). Although inferred from previous studies (e.g., Kean et al, 2011; Wells, 1987), the role of decreasing sediment availability can now be explored more fully with the use of high‐resolution change detection techniques such as terrestrial laser scanning (herein referred to as TLS) (e.g., Schmidt et al, 2011; Staley et al, 2014) and unmanned aerial vehicle Structure‐from‐Motion (herein referred to as SfM) (Ellett et al, 2019). TLS methods are able to resolve surface changes down to less than a centimeter such as those associated with widespread hillslope erosion on burned hillslopes (e.g., DeLong et al, 2018; Staley et al, 2014), and UAV‐based SfM is able to resolve changes on the order of a decimeter (e.g., Barnhart et al, 2019; Ellett et al, 2019) that would be associated with the erosion of large rills, gullies, and channels.…”
Section: Introductionmentioning
confidence: 99%
“…They showed how a runoff-generated debris flow can be triggered by low intensity precipitation, resulting in a large distributary fan. Importantly, this work also illustrates the contribution of post-fire erosion to long-term erosion rates Ellett et al (2019). documented a post-fire erosion rate of (6 mm yr À1 ), which is higher than the average erosion rate in the Idaho batholith region since the middle Holocene (5 mm yr À1 ).…”
mentioning
confidence: 60%
“…Sediment was first transported into swales through aeolian processes and then subsequently eroded by cold season hydrologic processes (rain-on-snow, rain-on-frozen soils, and snowmelt). Ellett et al (2019) 2) the presence of permafrost. Generally, they found that organic carbon tends to decrease in confined valleys and increase in unconfined valleys.…”
Section: Special Issue Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ellett et al (2019) page 3132, in the original published version, Figure 4 was incorrect and appears to be a duplicate of Figure 2. The figure caption is correctly presented but the corresponding figure was wrongly inserted.…”
Section: Figurementioning
confidence: 99%